DINAMIKA DUKUNGAN SOSIAL PADA PEREMPUAN POSITIF HIV/AIDS - Theressa Avelia Silubun; Rijal Abdillah (Universitas Pahlawan, 2022)
Someone who has HIV/AIDS will have the HIV/AIDS virus all his life so that it becomes a deadly disease. This situation certainly shapes people’s behavior towards people with HIV/AIDS (ODHA) which has an impact on the psychological. ODHA will tend to hide their status, feel isolated, unneeded, have no shelter, and have suicidal thoughts. Therefore, to reduce these negative risks, support from various parties especially families in treatment and care so that those with HIV/AIDS are able to endure their lives with enthusiasm. This study intends to exploration the dynamics of social support for HIV/AIDS positive women. The purpose of this research is to answer one questions. How are the dynamics of social support for HIV/AIDS positive women. By using data research through purpossive sampling and using phenomenological approach as part of analyzing data for two of research subjects and two sources, the researcher reaches some conclusions. First, there are emotional support from the closest person who is willing to listen and understand without prejudice and differentiation. Second, appreciation support that makes the subject feel valuable and feel safe. Third, instrumental support such as subsidizing drug costs. Fourth, information support related to HIV / AIDS. Fifth, peer group support obtained from fellow people with HIV/AIDS. Keywords: Social Support, HIV/AIDS